2015
DOI: 10.11648/j.ajls.s.2015030601.13
|View full text |Cite
|
Sign up to set email alerts
|

A Key for Identification of Spiders at Qena Governorate, Upper Egypt

Abstract: Spiders are one of the more diverse arthropod taxa, ranking seventh in global diversity, which makes them a fascinating group to study [1]. The correct identification of many spider species is considered problematic due to complex variation in morphology [2]. The Egyptian spider fauna are incompletely known due to scarcity of studies on this group especially in Upper Egypt. So, the present key for identifying terrestrial spiders at Qena Governorate is a part of a comprehensive study conducted at the region to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
3
2
Order By: Relevance
“…All of the recorded families in this research were recovered in the present study except family Oxyopidae. Whereas, 8 families: Dysderidae, Dictynidae, Eresidae, Filistatidae, Liocranidae, Pisauridae, Sicariidae, Titanoecidae and Uloboridae were recorded in the present study did not show in [30] survey. [31].…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…All of the recorded families in this research were recovered in the present study except family Oxyopidae. Whereas, 8 families: Dysderidae, Dictynidae, Eresidae, Filistatidae, Liocranidae, Pisauridae, Sicariidae, Titanoecidae and Uloboridae were recorded in the present study did not show in [30] survey. [31].…”
Section: Discussioncontrasting
confidence: 73%
“…Whereas, 8 families: Dysderidae, Dictynidae, Eresidae, Filistatidae, Liocranidae, Pisauridae, Sicariidae, Titanoecidae and Uloboridae were recorded in the present study did not show in [30] survey. [31].…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Investigators suggest that morphological identification of spiders could be confirmed by molecular methods [20,21]. To the best of our knowledge, this is the first molecular study on spiders in Iran and this would be a base for future alternative studies like assessment of the human protection against the specific Iranian L. tredecimguttatus anti-venom.…”
Section: Discussionmentioning
confidence: 91%
“…The Egyptian spider fauna is incompletely known due to scarcity of studies on this group, particularly in Upper Egypt. So, the key for identifying terrestrial spiders at Qena Governorate is a part of a comprehensive study conducted in the region by Obuid-Allah et al (2015). Fauna of Arabia mainland and Yemen which defined by Knoflach and Harten (2002).…”
Section: Introductionmentioning
confidence: 99%